Effect of Hyperalimentation and Insulin-Treated Hyperglycemia on Tyrosine Levels in Very Preterm Infants Receiving Parenteral Nutrition. (January 2014) - Mayes, Kelly; Tan, Maw; Morgan, Colin
Background : Hyperalimentation describes the increase in glucose, amino acids (AAs), and lipid intake designed to overcome postnatal growth failure in preterm infants. Preterm infants are dependent on phenylalanine metabolism to maintain tyrosine levels because of tyrosine concentration limits in parenteral nutrition (PN). We hypothesized that hyperalimentation would increase individual AA levels when compared with the control group but avoid high phenylalanine/tyrosine levels. Aim : To compare the plasma AA profiles on days 8–10 of life in preterm infants receiving a hyperalimentation vs a control regimen. Methods : Infants <29 weeks' gestation were randomized to receive hyperalimentation (30% more PN macronutrients) or a control regimen. Data were collected to measure macronutrient (including protein) intake and PN intolerance, including hyperglycemia, insulin use, urea, and AA profile. Plasma profiles of 23 individual AA levels were measured on days 8–10 using ion exchange chromatography. Results : One hundred forty-two infants were randomized with 118 AA profiles obtained on days 8–10. There were no differences in birth weight or gestation between groups. There was an increase ( P < .05) in 8 of 23 median individual plasma AA levels when comparing hyperalimentation (n = 57) with controls (n = 61). Only tyrosine levels (median; interquartile range) were lower with hyperalimentation: 27 (15–52) µmol/L vs 43 (24–69) µmol/L ( P < .01). Hyperalimentation resulted in more insulin-treated hyperglycemia. No difference between the groups was apparent in tyrosine levels when substratified for insulin-treated hyperglycemia. All insulin vs no insulin comparisons showed lower tyrosine levels with insulin treatment ( P < .01). Conclusion : Hyperalimentation can result in paradoxically low plasma tyrosine levels associated with an increase in insulin-treated hyperglycemia.